2008
DOI: 10.1038/ng.226
|View full text |Cite
|
Sign up to set email alerts
|

MYH9 is a major-effect risk gene for focal segmental glomerulosclerosis

Abstract: The increased burden of chronic kidney and end-stage kidney diseases (ESKD) in populations of African ancestry has been largely unexplained. To identify genetic variants predisposing to idiopathic and HIV-1-associated focal segmental glomerulosclerosis (FSGS), we carried out an admixture-mapping linkage-disequilibrium genome scan on 190 African American individuals with FSGS and 222 controls. We identified a chromosome 22 region with a genome-wide logarithm of the odds (lod) score of 9.2 and a peak lod of 12.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
633
5
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 643 publications
(668 citation statements)
references
References 50 publications
16
633
5
6
Order By: Relevance
“…In addition to the de novo identified podocyte-specific genes, genes that have been shown by genetic or functional studies to be causally involved in hereditary glomerular diseases and chronic progressive renal failure, including DACH1 (nanodissection rank 184) (Köttgen et al 2010), APOL1 (rank 185) (Genovese et al 2010;Kopp et al 2011), VEGFA (rank 247) (Eremina et al 2008;Köttgen et al 2010), and MYH9 (rank 260) (Kao et al 2008;Kopp et al 2008), were ranked highly by our method. During the preparation of this manuscript, MYO1E (rank 75) was reported to be associated with autosomal-recessive, glucocorticoid-resistant nephrotic syndrome (Mele et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the de novo identified podocyte-specific genes, genes that have been shown by genetic or functional studies to be causally involved in hereditary glomerular diseases and chronic progressive renal failure, including DACH1 (nanodissection rank 184) (Köttgen et al 2010), APOL1 (rank 185) (Genovese et al 2010;Kopp et al 2011), VEGFA (rank 247) (Eremina et al 2008;Köttgen et al 2010), and MYH9 (rank 260) (Kao et al 2008;Kopp et al 2008), were ranked highly by our method. During the preparation of this manuscript, MYO1E (rank 75) was reported to be associated with autosomal-recessive, glucocorticoid-resistant nephrotic syndrome (Mele et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic approaches identified novel players in renal fibrosis (157), such as the homeodomain interacting protein kinase 2 (HIPK2) in HIV transgenic mice (158). In patients with chronic kidney disease or glomerulosclerosis, genome-wide association studies (GWAS) identified several susceptibility loci (159)(160)(161), including in genes for myosin heavy chain 9 (MYH9) and uromodulin (Tamm-Horsfall protein, UMOD). Both proteins are expressed in TECs, the latter exclusively.…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 99%
“…Epidemiologic research of glomerular diseases is limited due to the rarity of individual disease types, the difficulty in correctly diagnosing them, and the lack of accurate disease data. Most epidemiologic studies rely upon biopsy results for accurate disease information (2)(3)(4).…”
mentioning
confidence: 99%